Carotid Intima-Media Thickness and Circulation Markers of Inflammation in Patients With Depression. (March 2020) - Saleptsis, Vasileios; Papaliaga, Maria; Spanos, Konstantinos; Kouvelos, George; Labropoulos, Nicos; Halaris, Angelos; Giannoukas, Athanasios
Objective: Growing evidence indicates that depressive disorders (DDs) are an important risk factor for atherosclerosis. The aim of this study was to evaluate the presence of common carotid artery (CCA) intima-media thickness (IMT) and circulation inflammation markers in patients with DD. Methods: A cross-sectional prospective study was undertaken comparing 40 patients with DD to 40 individuals free of depression, matched for age and gender. The Beck Depression Inventory questionnaire, serum total cholesterol, triglycerides, high-sensitivity C-reactive protein, interleukin-6, tumor necrosis factor α, P-selectin, and E-selectin levels were measured. The CCA-IMT was assessed with duplex sonography. Results: Patients with DD were more likely to smoke (65% vs 40%; P = .03) and have higher levels of serum total cholesterol (211 mg/dL vs 181 mg/dL; P = .010), triglycerides (138 mg/dL vs 97 mg/dL; P = .005), and P-selectin (0.87 ng/mL vs 0.61 ng/mL; P = .05) and lower levels of interleukin 6 (4.4 ± 2.1 pg/mL vs 10.3 ± 1.1 pg/mL; P = .002). The CCA-IMT was similar in both groups (0.07 ± 0.02 cm vs 0.06 ± 0.01 cm; P = .31). Among those with CCA-IMT in the upper quartile, subjects in the DD group had lower levels of interleukin 6 ( P = .05) and triglycerides ( P = .01) and higher levels of soluble P-selectin ( P = .03). Conclusion: Patients with DD do not present with higher CCA-IMT than a control group, although smoking and a higher level of serum lipids are present. Inflammatory biomarkers seem to be higher in patients with DD.